Carbonic anhydrase IV expression in rat and human gastrointestinal tract regional, cellular, and subcellular localization. - Fleming, R E (1995)
Carbonic anhydrase IV (CA IV) is a glycosylphosphatidylinositol-linked isozyme previously identified on the surface of renal tubular epithelium and certain populations of vascular endothelium. This report identifies the regional, cellular, and subcellular localization of CA IV in the rat gut. Northern blot and RT-PCR analyses demonstrated little CA IV expression in stomach or proximal small intestine, but abundant expression in distal small and large intestine. In contrast, CA II mRNA was abundant in stomach, decreased in proximal small intestine, low in distal small intestine, and abundant in large intestine. CA I mRNA was detected only in large intestine. The regional distribution of CA IV activity correlated with distribution of CA IV mRNA. Immunohistochemistry localized CA IV to the apical plasma membrane of the mucosal epithelium in distal small intestine and large intestine. Signal intensity was greatest in colon. CA IV was additionally found in submucosal capillary endothelium of all gastrointestinal regions. Immunohistochemical findings in human stomach and colon paralleled those in the rat. These studies demonstrate pre-translational isozyme-specific regulation of CA expression along the cranial-caudal axis of the gastrointestinal tract. The regional, cellular, and subcellular localizations are consistent with participation of CA IV in the extensive ion and fluid transport in the distal small and large intestine.